2021
DOI: 10.2147/ijgm.s335713
|View full text |Cite
|
Sign up to set email alerts
|

The Downregulation of Prognosis- and Immune Infiltration-Related Gene CYFIP2 Serves as a Novel Target in ccRCC

Abstract: Background: Increasing evidence indicated that the aberrant expression of the cytoplasmic FMR1-interacting protein (CYFIP) family might possess critical role and potential functions in cancer. But the role of CYFIP2 in clear cell renal cell carcinoma (ccRCC) is still uncharacteristic. Methods: We investigated the Cancer Genome Atlas Kidney Clear Cell Carcinoma (TCGA-KIRC) database for the expression profile, clinicopathological variables, clinical prognosis information, and promoter methylation levels of CYFIP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…In addition, Saller et al reported CYFIP2 as a candidate p53 target gene in H1299 lung cancer cells ( 46 ), and Jackson et al verified in DLD1 colorectal adenocarcinoma cells that CYFIP2 can act as a p53-inducible gene to promote apoptosis in colorectal adenocarcinoma cells ( 47 ). Also, Tong et al found that CYFIP2 expression was decreased in clear cell renal cell carcinoma and was associated with poorer clinicopathological parameters of clear cell renal cell carcinoma patients ( 48 ). CYFIP2 activates the cell death program to inhibit the proliferation of tumor cells, indicating that CYFIP2 is a potent tumor suppressor.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Saller et al reported CYFIP2 as a candidate p53 target gene in H1299 lung cancer cells ( 46 ), and Jackson et al verified in DLD1 colorectal adenocarcinoma cells that CYFIP2 can act as a p53-inducible gene to promote apoptosis in colorectal adenocarcinoma cells ( 47 ). Also, Tong et al found that CYFIP2 expression was decreased in clear cell renal cell carcinoma and was associated with poorer clinicopathological parameters of clear cell renal cell carcinoma patients ( 48 ). CYFIP2 activates the cell death program to inhibit the proliferation of tumor cells, indicating that CYFIP2 is a potent tumor suppressor.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research demonstrated that Cyfp 2 might play a critical role and have potential functions in cancers, such as gastric cancer [29] and colorectal adenocarcinoma [30]. Previous studies indicated CYFIP2 was downregulated in ccRCC patients due to its DNA methylation, and it was involved in the metabolic reprogramming, the EMT pathway, and immune infltration processes in ccRCC by its DNA methylation [31]. Te eukaryotic initiation factor 4A (eIF4A) family plays a vital role in many cancers [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis unearthed that CYFIP2 was upregulated and validated in peripheral blood mononuclear cell samples of RA patients, creating a novel gene signature in RA diagnostic and therapeutic interventions ( 30 ). An investigation focused on the downregulation of CYFIP2 in clear cell renal cell carcinoma (ccRCC) revealed that several immune markers were critically correlated with CYFIP2 expression, especially with CD4+ cells and CD8+ cells, which could act as a tumor suppressor gene in ccRCC and create a novel strategy in clinical treatment ( 31 ). Except for RCC, current research about CYFIP2 was mainly concentrated on neurons and encephalopathy ( 32 , 33 ), and more attention should be paid to RA.…”
Section: Discussionmentioning
confidence: 99%